Isorhynchophylline Exerts Antinociceptive Effects on Behavioral Hyperalgesia and Allodynia in a Mouse Model of Neuropathic Pain: Evidence of a 5-HT1A Receptor-Mediated Mechanism - Gao, Ke-Xin; Zhao, Qing; Wang, Gang-Ren; Yu, Lu; Wu, Jia-Yi; Zhao, Xin (Frontiers in Pharmacology, 2020)
Chronic neuropathic pain poses a significant health problem, for which effective therapy or antidote is lacking. The current work aimed to investigate the potential antinociceptive efficacy of isorhynchophylline, an oxindole alkaloid, against neuropathic pain and elucidate mechanisms. Male C57BL/6J mice were subjected to chronic constriction injury (CCI) by loose ligation of their sciatic nerves. Following CCI surgery, the neuropathic mice developed pain-like behaviors, as shown by thermal hyperalgesia in the Hargreaves test and tactile allodynia in the von Frey test. Repetitive treatment of CCI mice with isorhynchophylline (p.o., twice per day for two weeks) ameliorated behavioral hyperalgesia to thermal stimuli and allodynia to tactile stimuli in a dose-dependent fashion (5, 15 and 45 mg/kg). The isorhynchophylline-triggered antinociception seems serotonergically dependent, since its antinociceptive actions on neuropathic hyperalgesia and allodynia were totally abolished by chemical depletion of spinal serotonin by PCPA, whereas potentiated by 5-HTP (a precursor of 5-HT). Consistently, isorhynchophylline-treated neuropathic mice showed escalated levels of spinal monoamines especially 5-HT, with depressed monoamine oxidase activity. Moreover, the isorhynchophylline-evoked antinociception was preferentially counteracted by co-administration of 5-HT1A receptor antagonist WAY-100635. In vitro, isorhynchophylline (0.1-10 nM) increased the Emax (stimulation of [35S] GTPγS binding) of 8-OH-DPAT, a 5-HT1A agonist. Of notable benefit, isorhynchophylline was able to correct co-morbidly behavioral symptoms of depression and anxiety evoked by neuroapthic pain. Collectively, these findings confirm, for the first time, the disease-modifying efficacy of isorhynchophylline on neuropathic hypersensitivity, and this effect is dependent on spinal serotonergic system and 5-HT1A receptors.